Port wine stain treatment outcomes have not improved over the past three decades. (23rd April 2019) - van Raath, M.I.; Chohan, S.; Wolkerstorfer, A.; van der Horst, C.M.A.M.; Storm, G.; Heger, M.
Abstract: Background: Since the early '80s, the pulsed dye laser has been the standard treatment tool for non‐invasive port wine stain (PWS) removal. In the last three decades, a considerable amount of research has been conducted to improve clinical outcomes, given that a fraction of PWS patients proved recalcitrant to laser treatment. Whether this research actually led to increased therapeutic efficacy has not been systematically investigated. Objective: To analyse therapeutic efficacy in PWS patients globally from 1986 to date. Methods: PubMed was searched for all available PWS trials. Studies with a quartile percentage improvement scale were included, analysed and plotted chronologically. Treatment and patient characteristics were extracted. A mean clearance per study was calculated and plotted. A 5‐study simple moving average was co‐plotted to portray the trend in mean clearance over time. The data were separately analysed for multiple treatment sessions in previously untreated patients. Results: Sixty‐five studies were included (24.3% of eligible studies) comprising 6207 PWS patients. Of all patients, 21% achieved 75–100% clearance. Although a few studies reported remarkably good outcomes in a subset of carefully selected patients, there was no upward trend over time in mean clearance. Conclusion: The efficacy of PWS therapy has not improved in the past decades, despite numerous technical innovations and pharmacological interventions. With an unwavering patient demand for better outcomes, the need for development and implementation of novel therapeutic strategies to clear all PWS is as valid today as it was 30 years ago.